(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Migrant workers, moving in search of jobs, encounter various challenges and shifts within the fisheries sector. This study delves into three crucial facets: challenges faced by these workers, socio-economic impacts on local communities, and the effects of working conditions. Fisheries migrants encounter hurdles like language barriers, poor living conditions, discrimination, and limited healthcare access. Transitioning into this industry presents difficulties such as work-related hazards, unequal treatment, and delayed wages. Most of the migrant fishermen originate from Uttar Pradesh, primarily married and possessing over 1-3 years of experience. The study finds no significant socio-economic gap between married and unmarried migrants. Workers aged 35-45 face heightened work stress and safety concerns, while those below 25 experience delays in receiving their share of the catch. Improving housing infrastructure and providing adequate laundry facilities and clean water sources within fishing sectors can significantly enhance living conditions and promote hygiene among migrant workers. These challenges paint a complex picture that deeply affects the socio-economic fabric of these migrant workers. By examining these challenges this study aims to provide a comprehensive understanding of the intricate realities faced by fisheries migrants and their migration experiences.